2016
DOI: 10.18632/oncotarget.10885
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional collagen scaffold cell culture system for screening anti-glioma therapeutics

Abstract: Three-dimensional (3D) culture, which can simulate in vivo microenvironments, has been increasingly used to study tumor cell biology. Since most preclinical anti-glioma drug tests still rely on conventional 2D cell culture, we established a collagen scaffold for 3D glioma cell culture. Glioma cells cultured on these 3D scaffolds showed greater degree of dedifferentiation and quiescence than cells in 2D culture. 3D-cultured cells also exhibited enhanced resistance to chemotherapeutic alkylating agents, with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 47 publications
8
58
0
Order By: Relevance
“…Thus, 3D culture may be a powerful tool in tumor and relevant drug research. Marked advances have been made in the basic development of 3D tumor models so far, and prominent studies using 3D tumor cell models to simulate the tumor microenvironment or assess drug delivery in the past 5 years are summarized in Table I (6,8,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Considering the advantages of 3D tumor models, the present review provides an overview of the methods and techniques successfully devised for practicing 3D tumor cell culture.…”
Section: Current Preclinical Tumor Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, 3D culture may be a powerful tool in tumor and relevant drug research. Marked advances have been made in the basic development of 3D tumor models so far, and prominent studies using 3D tumor cell models to simulate the tumor microenvironment or assess drug delivery in the past 5 years are summarized in Table I (6,8,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Considering the advantages of 3D tumor models, the present review provides an overview of the methods and techniques successfully devised for practicing 3D tumor cell culture.…”
Section: Current Preclinical Tumor Modelsmentioning
confidence: 99%
“…2). For example, glioblastoma U87 cells are fusiform, flat and epithelioid in 2D culture, but grew as small, round or ovoid cells and formed complex structures with cilia or microvilli on their surface in 3D scaffold culture (32).…”
Section: Multicellular Tumor Spheroids (Mcts)mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to recapitulate such cell microenvironments in vivo, three-dimensional (3D) culture has been alternatively used as in vitro tumor models, which can simulate in vivo cell behaviors, and provide more comparable and reliable results (8). Several 3D in vitro glioblastoma models have been established using extracellular matrix-based scaffolds and elucidated the dramatic differences in terms of cell proliferation, morphology, and drug resistance between 2D and 3D glioblastoma cells in culture (9)(10)(11). Our previous study reported the up-regulation of genes associated with stemness and differentiation, and vascular endothelial growth factor (VEGF) angiogenesis factor in 3D glioblastoma, which might play important roles in the enhancement of drug resistance (11).…”
mentioning
confidence: 99%
“…Second, cell retrieval from polystyrene scaffolds is never 100% effective, and cells retrieved may artificially select subpopulations with more invasive capacity or those that are more loosely attached to the matrix, making this system inadequate for cell maintenance or for experiments requiring cell suspensions such as FACS. Another group recently demonstrated that a 3D collagen scaffold enables growth of GBM cells that better recapitulate the gene expression of GSCs, as well as more faithfully reflect how tumor cells respond to alkylating chemotherapy 102 . As with matrigel, the ECM engulfing GBM tumors contain little collagen, rendering this system as a suboptimal representation of GBM tumor microenvironment.…”
Section: D Scaffoldsmentioning
confidence: 99%